Is Secularization a Pervasive Trend in Europe?: The Effects of the Ideological and Denominational Divides in Europe 2002–2016 - Meulemann, Heiner (Journal of religion in Europe, 2023)
Between 2002 and 2016, church attendance and self-attributed religiosity declines linearly, if all countries included in the European Social Survey are taken together. This analysis differentiates within Europe between two ideological and three denominational divides. Two questions are examined. First, is secularization pervasive across these groups? Second, how pervasive does secularization remain as a macro-level trend, when cohort membership and other individual-level qualities are controlled for? We find that the trend in secularization is well-explained by cohort succession in Western as well as in Catholic and Protestant countries. In Eastern Orthodox countries, however, an increase in religiosity is observed, which cannot be explained by individual-level properties. We speculate that it is triggered by a coalition of national churches and political elites.